Analytic Approximation of Energy Resolution in Cascaded Gaseous Detectors. (14th April 2016) - Varga, Dezső
Abstract : An approximate formula has been derived for gain fluctuations in cascaded gaseous detectors such as Gas Electron Multipliers (GEMs), based on the assumption that the charge collection, avalanche formation, and extraction steps are independent cascaded processes. In order to test the approximation experimentally, a setup involving a standard GEM layer has been constructed to measure the energy resolution for 5.9 keV gamma particles. The formula reasonably traces both the charge collection and the extraction process dependence of the energy resolution. Such analytic approximation for gain fluctuations can be applied to multi-GEM detectors where it aids the interpretation of measurements as well as simulations.